(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article is devoted to the formation and principle of the formation of the tourist terminology of the Uzbek language, such internal, external, linguistic factors as mastery, specialization of language units and the creation of new terms are used.